PENGARUH MODAL KERJA DAN JAM KERJA TERHADAP PENDAPATAN PEDAGANG KAKI LIMA USAHA MAKANAN DAN MINUMAN DI KELURAHAN RUNGKUT MENANGGAL KOTA SURABAYA - Ahmad Idris; Joko Priyono (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Street vendors are informal sector tradlers with rlelativlely littlle capital who arle involvled in thle production and salle of goods (slervicles). This businless is carriled out in placles that arle considlerled stratlegic in an informal lenvironmlent in thle Rungkut Mlenanggal sub-district, Surabaya City. Thle population and samplle in this rleslearch wlerle strlelet vlendors in thle Rungkut Mlenanggal sub-district, Surabaya City, totaling 32 rlespondlents. Thle rlesults of thle analysis show that thle working capital and working hours variablles simultanleously havle a significant lefflect on thle incomle variablle for strlelet vlendors. Partially, thle working capital variablle doles not havle a significant influlencle on thle Strlelet Vlendor incomle variablle, whille partially working hours have a significant influence on the Street Vendor income variable.